Monoparentalidade feminina no Brasil: dinâmica das trajetórias familiares - Márcio Mitsuo Minamiguchi (2017)
In a demographic approach, the way a population is distributed into different family categories in a given period may be thought as resulting from its successive cohorts family formation experiences. From this perspective, this thesis aims to assess single motherhood as a family transition characterized by events related to its entry and exit into this family arrangement category in Brazil. Due to the lack of data bases designed to allow direct measuring of the families formation and dissolution processes, this thesis develops an indirect measuring approach from 1991, 2000 and 2010s Brazilian demographic census available data. It establishes a method for measuring the lone parental dynamics intensity as well as it points the heterogeneity of single motherhood as a result of the time period and social context in which they take place. Therefore, a differential assessment is needed having the education background as an essential element in order to consider the way family dynamics occurs in these different contexts